Evaluasi Program Pemberian Beasiswa Kerjasama Memorandum of Understanding (MoU) Pemerintah Kabupaten Labuhanbatu Utara dan Dampaknya terhadap Mahasiswa Penerima Beasiswa - Burhanuddin Sagala; Dara Aisyah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to evaluate the implementation of a scholarship program established through a Memorandum of Understanding (MoU) between the Government of Labuhanbatu Utara Regency and partner universities, and to analyze its impact on the educational quality of scholarship recipients. The study is motivated by the low participation rate in higher education in the region, despite the government’s efforts to improve human resource quality through scholarship initiatives. Fluctuations in the number of recipients and implementation challenges highlight the need for a comprehensive evaluation. This research employs a mixed-methods approach combining qualitative and quantitative data. Qualitative data were collected through in-depth interviews, observations, and document analysis involving key informants such as program administrators and scholarship recipients. Quantitative data were obtained through surveys using questionnaires. The evaluation uses the CIPP model (Context, Input, Process, Product) to assess policy context, resources, implementation processes, and program outcomes. The findings indicate that the MoU-based scholarship program positively contributes to improving access and quality of education, although some limitations remain. Overall, the program represents a strategic effort to enhance human resources, reduce educational disparities, and strengthen the competitiveness of the younger generation.